Podcasting Agriculture News: Producing Portable Audio News for Farmers and Ranchers - Blair L. Fannin (Journal of Applied Communications, 2006)
This article focuses on an emerging technology called podcasting as a new source of Web audio news distribution. Podcasting derives from the words iPod (Apple Inc.'s MP3 audio player) and broadcasting. Audio content, such as news, is compressed into MP3 audio file format and can be automatically downloaded to a computer by subscribing to a Web site's RSS (Really Simple Syndication) feed. The audio file can be transferred to a portable MP3 player, which can be listened to at the user's convenience in just about any setting. The audio files can also be burned onto a CD-ROM and played in an automobile, or listened to on a desktop computer. There is an absence of agriculture news in some rural radio markets; podcasting can fill that void with a variety of news and educational programming, targeting both agricultural producers and the general public. Podcasting is an attractive technology to land-grant institutions with news divisions. The technology can be easily implemented without purchasing expensive transmitters and satellite time. Most institutions already have computers and servers, which are the only tools necessary to begin podcasting. Texas A&M University System Agricultural Communications adopted the technology in October 2004, targeting agricultural producers, general news consumers, and news media. Though it is still a new technology, podcasting has been embraced by the mass media, including CNN, The New York Times, The Wall Street Journal, and other national news organizations. This article provides more information about the Texas A&M experience with this. emerging medium.